The Effect of Price and Service Quality on Customer Satisfaction of PT Showbitz Mitra Utama Event Organizer in Medan City - Husnia, Syafika; Tarigan, Jenny Sari (Journal of Economics and Social Sciences (JESS), 2025)
Every company has a goal to win the competition and maximize company profits by attracting consumer interest from the suitability of the price set proportional to what will be given to the company and the quality of service that matches customer expectations or expectations. In other words, there are two main factors that affect service quality, namely expected service and perceived service. This study aims to determine how the effect of price and service quality on customer satisfaction of PT Showbitz Mitra Utama event organizer services. This type of research is quantitative with the data sources used, namely literature study and distributing questionnaires. The sample in this study were 35 respondents with saturated sampling technique. The data analysis technique used in this research is multiple linear regression with partial data hypothesis testing (t test), simultaneous test (F test) and the coefficient of determination using SPSS version 25. From the results of the t test, it shows that price and service quality partially have a positive and significant effect on customer satisfaction for event organizer services. The results of the F test show that price and service quality simultaneously have a positive and significant effect on customer satisfaction of event organizer service users. The Adjusted R Square (R2) results show that price and service quality are able to influence customer satisfaction of event organizer service users by 53.6% and the remaining 46.4% can be explained by factors not examined in this study such as promotional variables, promotional variables, location, facilities, company image, personal selling, product variations and so on which are not examined in this study.